Prevalence of the Functional Dyspepsia and Associated Factors in the Chronic Hemodialysis Patients of the National Teaching Hospital “HKM” of Cotonou - Sehonou, Jean Jacques; VIGAN, JACQUES; AGBOTON, BRUNO; MASSI, Gbètondji Michel (My University, 2015)
Aim: To study the functional dyspepsia in chronic hemodialysis patients of CNHU-HKM of Cotonou. Methods: This descriptive, analytical and cross-sectional study ran from 1 September 2013 to 28 February 2014 in the University Clinic of Nephrology Dialysis of CNHU-HKM of Cotonou. It included all chronic renal failure patients on hemodialysis for at least 9 months prior to the survey. After identifying the patients with upper gastrointestinal disorders, we had submitted to clinical Rome III criteria for functional dyspepsia. Upper endoscopy was performed in patients with clinical criteria of functional dyspepsia. Clinical factors associated, paraclinical and therapeutic were sought by logistic regression in univariate analysis. Data were analyzed using EPI DATA version 3.1. Results: 1) One hundred and thirty-one haemodialysis patients had participated in the study (sex ratio: 1.5, average age 49.6 ± 12.4 years). 2) The prevalence was 71.8% for upper gastrointestinal disorders, 64.9% for dyspeptic syndrome and 1.5% for functional dyspepsia. 3) They were associated to clinical criteria of functional dyspepsia of Roma III, the presence of high blood pressure, hypocalcaemia, treatment with calcic inhibitors and iron supplementation. Conclusion: Functional dyspepsia is uncommon in hemodialysis. The search of an organic cause is imperative for every dyspepsia.
Keywords: Benin; Chronic Haemodialysis; Functional Dyspepsia; Dyspepsia; Upper Gastrointestinal Disorders